Evaluation of Different Sesame lines (Sesamum indicum L.) for Enhancing the Cropping Intensity and Productivity under Foot Hill Condition of Nagaland - Kumar, Rakesh; Hangsing, Neivah; Deka, Bidyut C; Kumar, Manoj (Indian Journal of Hill Farming, 2016)
Field experiment was carried out during the kharif season 2013 and 2014 at Agricultural Research Farm of ICAR Nagaland Centre Jharnapani to evaluate the growth and yields potential of 14 sesame lines. The main idea of the study is screening and selecting the high yielding lines of sesame, so as encourage and arouse farmer’s interest in its commercial cultivation under the foot hill condition of Nagaland. The experiment was laid out in randomized block design with three replications consisting of 14 sesame lines viz. IAVT-14-1, IAVT-14-2, IAVT-14-3, IAVT-14-4, IAVT-14-5, IAVT-14-6, IAVT-14-7, IAVT-14-8, IAVT-14-9, IAVT-14-10, IAVT-14-11, IAVT-14-12, IAVT-14-13 and local lines as check. Result indicated that significant variations were observed in growth and yield attributes of sesame lines during the experimentation. All the sesame lines showed the better performance and produced outstanding seed yield as compared to local lines (check). However, the sesame lines IAVT-14-1 produced significantly higher seed yield (708.33 kg/ha) as compared to the other lines.